DIGITAL ENVIRONMENT IN THE EDUCATIONAL PROCESS OF PEDAGOGICAL UNIVERSITIES - Gizatullina Olga Ivanovna; Abduvakhobov Iskander (Social science and innovation, 2024)
one of the trends in modern education is the creation of a digital educational environment. This article reveals the relevance of this trend for the pedagogical institute. One of the components of the digital educational environment, web resources, is considered in detail. Their types are described and examples of the most relevant subject resources for the introduction into the educational process are presented